230k views
3 votes
Use the functions f(x)=2x and g(x)=x^2+1 to find the value of each expression

1. f(g(3))
2. f(3)+g(4)
3. f(5)-2×g(1)​

User Makkusu
by
6.3k points

1 Answer

6 votes

Answer:

1. 20

2. 23

3. 6

Explanation:

We have that:

f(x) = 2x

g(x) = x² + 1

f(g(x)) is the composite function of f and g. So

f(g(x)) = f(x²-1) = 2(x²+1) = 2x² + 2

1. f(g(3))

f(g(x)) = 2x² - 2 = 2(3)² + 2 = 18 + 2 = 20

2. f(3)+g(4)

f(3) = 2(3) = 6

g(4) = 4² + 1 = 17

f(3) + g(4) = 6 + 17 = 23

3. f(5) - 2g(1)​

f(5) = 2(5) = 10

g(1) = (1)² + 1 = 2

f(5) - 2g(1) = 10 - 2*2 = 10 - 4 = 6

User Wagner
by
6.2k points